A Thioester-Containing Protein Controls Dengue Virus Infection in Aedes aegypti Through Modulating Immune Response - Weng, Shih-Che; Li, Hsing-Han; Li, Jian-Chiuan; Liu, Wei-Liang; Chen, Chun-Hong; Shiao, Shin-Hong (Frontiers in Immunology, 2021)
Complement-like proteins in arthropods defend against invading pathogens in the early phases of infection. Thioester-containing proteins (TEPs), which exhibit high similarity to mammalian complement C3, are thought to play a key role in the innate immunity of arthropods. We identified and characterized anti-dengue virus (DENV) host factors, in particular complement-like proteins, in the mosquito Aedes aegypti. Our results indicate that TEP1 limits DENV infection in Ae. aegypti. We showed that TEP1 transcription is highly induced in mosquitoes following DENV infection. Silencing TEP1 resulted in the up-regulation of viral RNA and proteins. In addition, the production of infectious virus particles increased in the absence of TEP1. We generated a transgenic mosquito line with a TEP1 loss-of-function phenotype under a blood meal-inducible promoter. We showed that viral RNA and titers increased in transgenic mosquitoes after an infectious blood meal. Interestingly, expression of transcription factor Rel2 and certain anti-microbial peptides (AMPs) were inhibited in transgenic mosquitoes. Overall, our results suggest that TEP1 regulates the immune response and consequently controls the replication of dengue virus in mosquitoes. This finding provides new insight into the molecular mechanisms of mosquito host factors in the regulation of DENV replication.